Factors contributing to men's grief following pregnancy loss and neonatal death: further development of an emerging model in an Australian sample - Kate Louise Obst; Melissa Oxlad; Clemence Due; Philippa Middleton (BMC, 2021)
Abstract Background Historically, men's experiences of grief following pregnancy loss and neonatal death have been under-explored in comparison to women. However, investigating men's perspectives is important, given potential gendered differences concerning grief styles, help-seeking and service access. Few studies have comprehensively examined the various individual, interpersonal, community and system/policy-level factors which may contribute to the intensity of grief in bereaved parents, particularly for men. Methods Men (N = 228) aged at least 18 years whose partner had experienced an ectopic pregnancy, miscarriage, stillbirth, termination of pregnancy for foetal anomaly, or neonatal death within the last 20 years responded to an online survey exploring their experiences of grief. Multiple linear regression analyses were used to examine the factors associated with men's grief intensity and style. Results Men experienced significant grief across all loss types, with the average score sitting above the minimum cut-off considered to be a high degree of grief. Men's total grief scores were associated with loss history, marital satisfaction, availability of social support, acknowledgement of their grief from family/friends, time spent bonding with the baby during pregnancy, and feeling as though their role of 'supporter' conflicted with their ability to process grief. Factors contributing to grief also differed depending on grief style. Intuitive (emotion-focused) grief was associated with support received from healthcare professionals. Instrumental (activity-focused) grief was associated with time and quality of attachment to the baby during pregnancy, availability of social support, acknowledgement of men's grief from their female partner, supporter role interfering with their grief, and tendencies toward self-reliance. Conclusions Following pregnancy loss and neonatal death, men can experience high levels of grief, requiring acknowledgement and validation from all healthcare professionals, family/friends, community networks and workplaces. Addressing male-specific needs, such as balancing a desire to both support and be supported, requires tailored information and support. Strategies to support men should consider grief styles and draw upon father-inclusive practice recommendations. Further research is required to explore the underlying causal mechanisms of associations found.